Anforderungen an eine standortübergreifende Biobanken-IT-Infrastruktur: Erhebung des Stakeholderinputs zum Aufbau eines Biobankennetzwerks der German Biobank Alliance (GBA) = Requirements for a cross-location biobank IT infrastructure : survey of stakeholder input on the establishment of a biobank network of the German Biobank Alliance (GBA) - Schüttler, Christina; Döllinger, Christoph (Der Pathologe, 2018)
BackgroundThe large number of biobanks within Germany results in a high degree of heterogeneity with regard to the IT components used at the respective locations. Within the German Biobank Alliance (GBA), 13 biobanks implement harmonized processes for the provision of biomaterial and accompanying data.ObjectivesThe networking of the individual biobanks and the associated harmonisation of the IT infrastructure should facilitate access to biomaterial and related clinical data.MethodsFor this purpose, the relevant target groups were first identified in order to determine their requirements for IT solutions to be developed in a workshop.ResultsOf the seven identified interest groups, three were initially invited to a first round of discussions. The stakeholder input expressed resulted in a catalogue of requirements with regard to IT support for (i) a sample and data request, (ii) the handling of patient consent and inclusion, and (iii) the subsequent evaluation of the sample and data request.ConclusionsThe next step is to design the IT solutions as prototypes based on these requirements. In parallel, further user groups are being surveyed in order to be able to further concretise the specifications for development.